Potential roles of inorganic phosphate on the progression of initially bound glucopyranose toward the nonenzymatic glycation of human hemoglobin: Mechanistic diversity and impacts on site selectivity. Issue 1 (1st January 2018) - Smith, Brandy A.; Mottishaw, Christina R.; Hendricks, Andria J.; Mitchell, Jason; Becker, Stephanie; Ropski, Pamela S.; Park, Bomina; Finkbeiner-Caufield, Marie; Garay-Nontol, Barbara; Holman, R.W.; Rodnick, Kenneth J.
Abstract: Nonenzymatic glycation (NEG) begins with the non-covalent binding of a glucopyranose to a protein. The bound glucopyranose must then undergo structural modification to generate a bound electrophile that can reversibly form a Schiff base, which can then lead to Amadori intermediates, and ultimately to glycated proteins. Inorganic phosphate (Pi) is known to accelerate the glycation of human hemoglobin (HbA), although the specific mechanism(s) of Pi as an effector reagent have not been determined. The aim of this study was to determine whether Pi and a glucopyranose can concomitantly bind to HbA and react while bound within the early, noncovalent stages to generate electrophilic species capable of progress in NEG. 31 P and 1 HNMR of model reactions confirm that bimolecular reactions between Pi and glucopyranose occur generating modified glucose electrophiles. Computations of protein/substrate interactions predict that Pi can concomitantly bind with a glucopyranose in HbA pockets with geometries suitable for multiple acid/base mechanisms that can generate any of four transient electrophiles. Pi-facilitated mechanisms in the noncovalent stages predict that the glycation of β-Val1 of HbA to HbA1c is a "hot spot" because the β-Val1 pocket facilitates many more mechanisms than any other site. The mechanistic diversity of the Pi effect within the early noncovalent stages of NEG predicts well the overall site selectivity observed from the in vivo glycation of HbA in the presence of Pi. These insights extend our basic understanding of the NEG process and may have clinical implications for diabetes mellitus and even normal aging.